Anotação semântica baseada em ontologia: um estudo do português brasileiro em documentos históricos do final do século XIX - Pereira, Juliana Wolf (2014)
This dissertation presents an approach to proceed with semantic annotation in historical documents from the 19th century that discuss the constitution of the mother tongue, the Portuguese Language in Brazil. The objective is to generate a group of semantically annotated documents in agreement with a domain ontology. To provide this domain ontology, the IntrumentoLinguistico Ontology was built, and it supported the process of automatic semantic annotation. The results obtained with the annotation were analyzed in comparison with the Gold Standard and they presented an elevated level of coincidence, between 0.86 and 1.00 for the Fl-score measure. Besides that, it was possible to locate new documents about the discussed domain in a sample of the Revistas Brazileiras. These results prove the efficacy of the approach of automatic semantic annotation.